2022
DOI: 10.1039/d2sc05520a
|View full text |Cite
|
Sign up to set email alerts
|

A carbapenem antibiotic inhibiting a mammalian serine protease: structure of the acylaminoacyl peptidase–meropenem complex

Abstract: The structure of porcine AAP (pAAP) in a covalently bound complex with meropenem was determined by cryo-EM to 2.1 Å resolution, showing the mammalian serine-protease inhibited by a carbapenem antibiotic....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…MEPM was reported to interact with VPA, with one of the mechanisms as the inhibition of β‐glucuronidase. A previous study indicated that VPA‐glucuronidase (VPA‐G) could be hydrolyzed back to VPA by acylpeptide hydrolase (APEH) [ 6 ], and the activity of APEH was reversibly and irreversibly suppressed by MEPM [ 7 ]. A decrease in activity of APEH by MEPM may cause increased urinary excretion of VPA‐G with concomitant reduction in plasma VPA concentration [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MEPM was reported to interact with VPA, with one of the mechanisms as the inhibition of β‐glucuronidase. A previous study indicated that VPA‐glucuronidase (VPA‐G) could be hydrolyzed back to VPA by acylpeptide hydrolase (APEH) [ 6 ], and the activity of APEH was reversibly and irreversibly suppressed by MEPM [ 7 ]. A decrease in activity of APEH by MEPM may cause increased urinary excretion of VPA‐G with concomitant reduction in plasma VPA concentration [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%